TranscriptFormer: A generative cell atlas across 1.5 billion years of evolution - James D. Pearce; Sara E. Simmonds; Gita Mahmoudabadi; Lakshmi Krishnan; Giovanni Palla; Ana-Maria Istrate; Alexander Tarashansky; Benjamin Nelson; Omar Valenzuela; Donghui Li; Stephen R. Quake; Theofanis Karaletsos (Science, 2026)
Single-cell transcriptomics is revolutionizing our understanding of cellular diversity, yet comparing transcriptional programs across the tree of life remains challenging. We developed TranscriptFormer, a family of generative foundation models trained on up to 112 million cells spanning 1.53 billion years of evolution across 12 species. We demonstrate state-of-the-art performance on cell type classification, even for species separated by over 685 million years of evolution, and zero-shot disease state identification in human cells. Developmental trajectories, phylogenetic relationships, and cellular hierarchies emerge naturally in TranscriptFormer’s representations without any explicit training on these annotations. This work establishes a powerful framework for quantitative single-cell analysis and comparative cellular biology, thus demonstrating that universal principles of cellular organization can be learned and predicted across the tree of life.